A bizarre Early Cretaceous enantiornithine bird with unique crural feathers and an ornithuromorph plough-shaped pygostyle - Min Wang (Nature Portfolio, 2017)
Although now extinct, Enantiornithes was the most diverse group of birds in the Mesozoic. Here, Wang and colleagues describe a new species of enantiornithine bird from 131 million years ago with features that suggest extensive diversification had occurred in the enantiornithines by this time.